Search for a Higgs boson in the mass range from 145 to 1000 GeV decaying to a pair of W or Z bosons - Khachatryan, V. (2015)
A search for a heavy Higgs boson in the H -> WW and H -> ZZ decay channels is reported. The search is based upon proton-proton collision data samples corresponding to an integrated luminosity of up to 5.1 fb(-1) at root s = 7 TeV and up to 19.7 fb(-1) at root s = 8 TeV, recorded by the CMS experiment at the CERN LHC. Several final states of the H -> WW and H -> ZZ decays are analyzed. The combined upper limit at the 95% confidence level on the product of the cross section and branching fraction exclude a Higgs boson with standard model-like couplings and decays in the range 145 < m(H) < 1000 GeV. We also interpret the results in the context of an electroweak singlet extension of the standard model.